Evaluating Quality of Life of Parents Having a Child with Disability - Ban, Rita Kumari; Luitel, Iswari; Regmi, Kalpana (Journal of Karnali Academy of Health Sciences, 2020)
Introduction: Disability is the condition of difficulty in carrying out daily activities normally and in taking part in social life due to problems in parts of the body and the physical system. Children with disabilities are one of the most marginalized and excluded groups in society. Facing daily discrimination in the form of negative attitudes, Estimates suggest that there are at least 93 million children with disabilities in the world, but numbers could be much higher. Method: A descriptive-analytical research design was used to identify the quality of life of parents/caretakers having a child with disability/ies in Illam district. Systematic random sampling was used and collected data from 244 participants. World Health Organization Quality of Life-Brief (WHOQOL-BREF) Questionnaire was adopted Association between the socio-demographic variables and four domains of WHOQOL was determined using one way ANOVA. In the end, multiple linear regression analysis was performed to find the predictors of domains of WHOQOL and to control the confounding effect. Results: The quality of parents having a child with a disability has a good quality of life in a social relationship mean 15.6±1.3.The physical domain is weakly correlated with the social domain. There is a moderate positive correlation between psychosocial and social domains. Cognitive disability means the score was highest on the social domain that is 14.91and lowest on the physical domain (13.87). Conclusion: To improve the quality of life of parents, health care and welfare professionals should focus on particular people with higher age group, disadvantaged and marginalized groups illiterate, those who are unmarried, divorced or separated and those engaged in agriculture and carry out interventions aimed at improving their quality of life. Keywords: Parents /caretaker, Quality of life, Children with disability